Secreted Factor R‐Spondin 2 is Involved in Refinement of Patterning of the Mammalian Cochlea. Issue 2 (22nd January 2013) - Mulvaney, J. F.; Yatteau, A.; Sun, W. W.; Jacques, B.; Takubo, K.; Suda, T.; Yamada, W.; Dabdoub, A.
<x xml:space="preserve">Abstract</x> Background: In the cochlea, patterning of the organ of Corti is tightly regulated to produce a single row of sound‐detecting inner hair cells and three rows of outer hair cells, which amplify and refine the signal. The recently identified R‐Spondin family of signaling molecules usually act as co‐activators of Wnt signaling; it is thought that they regulate turnover of Wnt receptors at the membrane. We sought to test whether R‐Spondins function in the developing cochlea. Results: Expression analysis of all four members of the R‐Spondin family showed that only R‐Spondin2 (Rspo2) is expressed in the cochlea during development of the sensory epithelium. Examination of an Rspo2−/− mouse showed that loss of Rspo2 results in an additional single row of outer hair cells and disruption of peripheral innervation pattern. Addition of Rspo2 recombinant protein to organotypic cochlear cultures resulted in a small but significant decrease in the number of outer hair cells. Conclusions:Rspo2 is required to limit the number of outer hair cells to three rows and for optimal arrangement of peripheral nerve fibers. The Rspo2 gain‐ and loss‐of‐function studies show that in the ear, Rspo2 function is not consistent with its assigned role as a Wnt potentiator. Developmental Dynamics 242:179–188, 2013. © 2012 Wiley Periodicals, Inc.